FACTORS INFLUENCING PATIENT SATISFACTION WITH HEALTHCARE SERVICES OFFERED IN SELECTED PUBLIC-PRIVATE PARTNERSHIP HOSPITALS IN DISTRICT BAJAUR, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Patient satisfaction can recognize certain parts of development in public sector healthcare systems. However, the quality-of-service delivery and the healthcare system in Pakistan are rarely evaluated from the standpoint of patient satisfaction. Our study illustrated the effectiveness of healthcare systems operating under Public-Private Partnership of district Bajaur, in Malakand Division of Khyber Pakhtunkhwa (KP) province of Pakistan (A tribal area with poor socioeconomic status), through interactions with tangible and intangible financial problems, doctor-patient interaction, and medical care based on patient satisfaction. A random sampling technique was used to gather primary data from the patients. Visitors to the outpatient sections of public-private partnership hospitals were study participants. The gathered data from 401 respondents via an organized questionnaire were analyzed using the confirmatory factor and multiple regression methods. The findings showed that financial easiness and Doctor-patient interaction had a considerable beneficial impact on patient satisfaction (p≤0.05), but medical care (p≥0.05) had a negligible impact. As a result, it is stated that there is a serious communication gap between a doctor and patient and that Pakistan's healthcare system lacks adequate financial support for the patients. As a result, these services require further development.